A Case of Successful Foraminotomy for Severe Bilateral C5 Palsy following Posterior Decompression and Fusion Surgery for Cervical Ossification of Posterior Longitudinal Ligament - Yoshifumi Kudo; Tomoaki Toyone; Toshiyuki Shirahata; Tomoyuki Ozawa; Akira Matsuoka; Yoichi Jin; Katsunori Inagaki (Case Reports in Orthopedics)
We report a very rare (5~7%) case of bilateral C5 palsy after cervical surgery. A 71-year-old male patient with cervical ossification of posterior longitudinal ligament (OPLL) with foraminal stenosis at bilateral C4/5 underwent posterior decompression and fusion surgery. After surgery, muscle weakness in his both deltoid and biceps was detected and gradually deteriorated to complete paralysis. Postoperative MRI showed sufficient decompression of the spinal cord and posterior shifting. Subsequently, an additional bilateral foraminotomy at C4/5 was performed, with a suspicion that bilateral foraminal stenosis at C4/5 may have been the cause of the paresis. After foraminotomy, muscular contraction was seen in both deltoid and biceps. Finally, complete motor recovery was achieved in a year. Although the gold standard procedure for the prevention and treatment of postoperative C5 palsy has not yet been established, an additional foraminotomy may be recommended for severe C5 palsy in cases of foraminal stenosis even after the occurrence of palsy.